Hubungan Keparahan Karies dengan Kualitas Hidup Ibu Hamil di Puskesmas Lubuk Buaya Kota Padang - Lutfia Khairani Zulfaneti; Gita Dwi Jiwanda Sovira; Susi Susi (Faculty of Dentistry Universitas Andalas, 2022)
Background: Dental caries can cause health problem among pregnant women including pain, eating and sleeping disturbances. It’s impact to the physical, social and mental health and also affected their disruption of the quality of life. Objectives: This study aims to determine the relationship between the severity of dental caries and the quality of life among pregnant women at the Lubuk Buaya Public Health Center. Methods: This is a cross-sectional study that involving 74 pregnant women. The quality of life was measured by the OHIP-14 questionnaire with seven assessment aspects. Quality of life categories is good (score ≤ 27) and poor (score >27). PUFA index was used to assess caries severity. PUFA categories is negative (PUFA = 0) and positive (PUFA ≥1). Data were analyzed by chi-square test. Results: This study show that almost respondents (55.4% of pregnant women) have PUFA (+), with mean 0.82 ± 0.86 SD. Most pregnant women have poor quality of life (51.4%). Some chief complaints discovered due to the severity of caries like disruption of tasting food 10.8%, discomfort during chewing the food 48.7%, feeling tension 10.5%, stopping while eating 56.8%, feeling not relaxed 17.6%, daily activities disturbance 8.1% and less happy 9.5%. Pregnant women with PUFA (-) had more good quality of life, while pregnant women with PUFA (+) had more poor quality of life (p < 0.05). Conclusion: Caries severity influence quality of life. This suggests the need for strategies to prevent and manage caries in pregnant woman.